What Do Turkish Students at Different Ages Know About Their Internal Body Parts Both Visually and Verbally? - CERRAH ÖZSEVGEÇ, Lale (Journal of Turkish Science Education, 2007)
The study aimed to seek the students understanding of their internal bodies. It was carried out in the East Black Sea Region of Turkey in two junior high schools. All data were gathered from 55grade 6 students (aged 12) and 57 grade 8 students (aged 14). The students were given an outline of body map and asked to draw which organs they have in their bodies. Once completed they to write the function of each organ. The drawings of the organs were analyzed according to their accurate characteristics such as presence, location, shape and function. The findings showed that the students of both grades had problems about the functions of the organs and other body structures.
Keywords: Biology Education; Understanding; Body Structures; Drawings